2000
DOI: 10.1111/j.1349-7006.2000.tb00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Germ‐line Mutation Analysis in Patients with von Hippel‐Lindau Disease in Japan: An Extended Study of 77 Families

Abstract: We have previously reported on the analysis of germ-line mutations in Japanese von HippelLindau disease (VHL) patients and found mutations in 26 families. We have now extended these studies to include an additional 41 VHL families. Germ-line mutation of the VHL gene was screened by DNA-SSCP, direct sequencing, and Southern blot analysis. To summarize all of the data we have studied in this and our previous report, germ-line mutations have been detected in 55 of 77 (73%) (type 1: 41 / 62 (66%) and type 2: 14/15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 25 publications
5
48
1
Order By: Relevance
“…Dinucleotide CpG hotspot mutations were found in both Japanese and Caucasian patients; however, the incidence was lower in Japanese patients [Yoshida et al, 2000]. Missense mutations occurred at a lower incidence overall in Japanese patients [Clinical Research Group for VHL in Japan, 1995;Shuin et al, 1995] and in VHL Type 1 Japanese families when compared to Western families [Fukino et al, 2000;Yoshida et al, 2000]. These variations could be attributed to possible environmental or ethnic factors.…”
Section: Ethnic Diversitymentioning
confidence: 95%
See 3 more Smart Citations
“…Dinucleotide CpG hotspot mutations were found in both Japanese and Caucasian patients; however, the incidence was lower in Japanese patients [Yoshida et al, 2000]. Missense mutations occurred at a lower incidence overall in Japanese patients [Clinical Research Group for VHL in Japan, 1995;Shuin et al, 1995] and in VHL Type 1 Japanese families when compared to Western families [Fukino et al, 2000;Yoshida et al, 2000]. These variations could be attributed to possible environmental or ethnic factors.…”
Section: Ethnic Diversitymentioning
confidence: 95%
“…Initially it was noted that phenotypes in Caucasian VHL families paralleled Japanese families for most mutations . Later studies by Yoshida et al [2000] found that mutations p.Arg113Ter, p.Gln132Ter, p.Leu158Val, and p.Cys162Tyr, which were previously associated with VHL Type 1 in Western cultures [Crossey et al, 1994a;Glavac et al, 1996;Maher et al, 1996;Zbar et al, 1996], were associated with VHL Type 2 in Japanese families [Clinical Research Group for VHL in Japan, 1995;Yoshida et al, 2000]. A study of 15 Korean patients showed the majority of VHL Type 1 mutations were nonmissense mutations, similar to those found in Japan and Western cultures [Cho et al, 2009].…”
Section: Ethnic Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although the mutation per se was not novel [8], we identified a loss of heterozygosity (LOH) in the affected adrenal gland of one of the patients in this family. This family case study may be helpful to understand the mechanism by which both HAB and PHE develop in VHLD.…”
mentioning
confidence: 97%